C D B! - Steig, William, 1907-2003. (New York : Windmill Books : Simon & Schuster, 1980)
Letters and words are used to create the sounds of words and simple sentences "4 u 2" figure out with the aid of illustrations.
Booklist.
4.0
3-6
Keywords: Word games -- Juvenile literature; Word games; Games